MODEL ARGUMEN PADA PARAGRAF ARGUMENTATIF DALAM ARTIKEL JURNAL TERINDEKS SINTA RUMPUN PENDIDIKAN EKSAKTA: PERSPEKTIF DOUGLAS WALTON - Antonius Nesi; Priska Filomena Iku (JIPD (Jurnal Inovasi Pendidikan Dasar), 2021)
Argument as a type of rhetoric of language is absolutely necessary in constructing, maintaining, and concluding ideas. With the existence of a solid argument construction in the body of scientific articles, the validity and reliability of facts, data, and inferences can be arguably justified. In this regard, this study aims to describe the argumentative paragraph model of the argumentative paragraphs in Sinta indexed journal articles for the exact education family. In collecting data, the observation method is used. The listening method is applied through reading and note-taking techniques. In data analysis, researchers made use of content analysis methods. Through data analysis, it was found that in the exact science education Sinta indexed journal there are three argument models, namely (1) verbal classification arguments, (2) rules arguments, and (3) witness arguments. The verbal classification argument model found includes (1) fact / perception arguments and (2) consequence arguments. The rule argument model found consists of (1) public opinion arguments, (2) personal opinion arguments, and (4) causal relationship arguments. Meanwhile, the findings of the witness argument model are (1) expert opinion argument, (2) analogy argument, and (3) fact-hypothesis argument. Based on these findings, it can be concluded that Douglas Walton’s argument models have not been fully accommodated in Sinta indexed journal articles for the exact education family. The authors of the articles are advised to continue to improve their publications by utilizing Walton's argument models in the hope that the resulting articles can be justified argumentatively-scientifically.